Low grade lignite upgrading using a novel dewatering-binderless briquetting combined process. Issue 5 (4th May 2023) - Cai, Luhui; Yu, Xiaodong; Zhao, Yuemin; Li, Gongmin; Luo, Zhenfu
ABSTRACT: The low-grade lignite reserve is large and it is an important basic material for coal gasification and liquefaction. However, it has high moisture content, high ash content, and low calorific value, and its use value is low without upgrading. The calorific value of lignite can be effectively improved by drying and dehydration. Meanwhile, due to the fine particle size of lignite powder, it is not convenient for storage and transportation, but it has certain utilization value. The efficient recovery and rational utilization of this part of the pulverized coal resources through coal powder briquetting increases its utilization value. In this paper, a study on the high-efficiency upgrading of low-grade lignite was carried out by using the combined process of multi-layer cross-flow drying and binderless pulverized coal briquetting. The migration and distribution law of lignite moisture in each drying bed was emphatically analyzed, and the influence of drying temperature and hot flue gas flow rate on drying effect under different treatment capacity was systematically studied. At the same time, the influence of coal powder with different particle size fraction on the briquetting load during the briquetting process and the influence of the −0.125 mm coal powder content on the quality of the briquetting product were analyzed. The drying and coal powder binderless briquetting test were carried out under the optimal parameters. The results show that the material moisture content decreases gradually from top to bottom along the bed height direction, and decreases gradually from the feed end to the discharge end for every layer. The dehydration rate is directly related to the feeding quantity. For the same drying temperature, the less the feeding quantity is, the lower critical point the optimal drying temperature reaches. During the binderless pulverized coal briquetting, as the briquetting load increases, the compressive strength of briquette products for different particle size fraction showed an increasing trend, while the falling strength increase firstly and then decreases. As the −0.125 mm fine coal content increases, the compressive strength increases, while the falling strength increases firstly and then decreases. The average drying temperature of hot flue gas is 200°C; the flow quantity of hot flue gas is 445–455 m 3 /h; the drying time is 12 minutes; the briquetting load is 120KN; the moisture content added is 12%. Under condition mentioned above, the moisture content of the dry lignite product is 9.75%; the ash content is 26.12%, and the calorific value is 23.47 KJ/g. For the briquetted lump coal, the total moisture content is 10.16%; the ash content is 25.78%; the calorific value is 23.21 KJ/g; the compressive strength is 2.56MPa and the falling strength is 93%.